ChemInform Abstract: 1, 3‐Dipolar Cycloaddition in a Series of 7‐Oxoalkyl‐1, 3, 7‐triazapyrenium Salts. Issue 14 (20th March 2013) - Borovlev, I. V.; Demidov, O. P.; Pisarenko, S. V.; Nemykina, O. A.; Saigakova, N. A.
Abstract A series of new 7‐substituted triazapyrenium salts (III) is synthesized, which undergo 1, 3‐dipolar cycloaddition reactions with chalcones furnishing previously unknown pyrrolotriazapyrenes [cf.